International Wheat Blast Consortium convened by WHEAT achieves early successes: Bundled research, resistant varieties in South Asia - CGIAR Research Program on Wheat (2018)
Since the discovery of wheat blast in Bangladesh in 2016, WHEAT, led by pathologist Pawan Singh, has coordinated 13+ partners to deliver a rapid response to mitigate the threat of the fungal disease in the region, which puts 7 million hectares of wheat growing area at risk in Bangladesh, India and Pakistan, according to a WHEAT 2018 ex-ante analysis (yield losses worth US$264M). A multi-pronged approach (regional convening, fundraising, education, release of resistant varieties) has led to initial outcomes.